Internet service providers responsibilities in botnet mitigation: a Nigerian perspective - Julius Olatunji Okesola; Marion Adebiyi; Tochukwu Osi-Okeke; Adeyinka Adewale; Ayodele Adebiyi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Botnet-based attack is dangerous and extremely difficult to overcome as all the primary mitigation methods are passive and limited in focus. A combine efforts of Internet Service Providers (ISPs) are better guides since they can monitor the traffic that traverse through their networks. However, ISPs are not legally banded to this role and may not view security as a primary concern. Towards understudying the involvement of ISPs in Botnet mitigation in Nigeria, this study elicited and summarized mitigation measures from scientific literatures to create a reference model which was validated by structured interview. Although, ISPs role is seen to be voluntary and poorly incentivized, the providers still take customers security very serious but concentrate more on preventive and notification measures.